2020
DOI: 10.1186/s12989-020-00379-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles effectively regulate autophagic cell death by activating autophagosome formation and interfering with their maturation

Abstract: Background With the development of zinc oxide nanoparticles (ZnO NPs) in the field of nanotechnology, their toxicological effects are attracting increasing attention, and the mechanisms for ZnO NPs neurotoxicity remain obscure. In an attempt to address concerns regarding neurotoxicity of ZnO NPs, we explored the relationship between free zinc ions, reactive oxygen species (ROS) and neurotoxic mechanisms in ZnO NPs-exposed PC12 cells. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Consistently, greater accumulation was observed in cells in response to FBPs-B(a)P100 and FBPs-B(a)P10, compared to cells upon FBPs-B(a)P0 (Figure 6A). In agreement with previous reports, 67,68 in a consequence, enhanced endocytosis and the fusion between lysosomes and phagosomes incurred injuries of the phagolysosomes and lysosomes in cells treated with FBPs, compared to the untreated cells, as reflected by the broken lysosomes visualized by the Lyso-Tracker Red DND-99 dye (Figure 6B, P < 0.05). To a greater extent, FBPs-B(a)P100 caused more reduction of lysosomal staining relative to that upon FBPs-B(a)P0 treatment (Figure 6B, P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…Consistently, greater accumulation was observed in cells in response to FBPs-B(a)P100 and FBPs-B(a)P10, compared to cells upon FBPs-B(a)P0 (Figure 6A). In agreement with previous reports, 67,68 in a consequence, enhanced endocytosis and the fusion between lysosomes and phagosomes incurred injuries of the phagolysosomes and lysosomes in cells treated with FBPs, compared to the untreated cells, as reflected by the broken lysosomes visualized by the Lyso-Tracker Red DND-99 dye (Figure 6B, P < 0.05). To a greater extent, FBPs-B(a)P100 caused more reduction of lysosomal staining relative to that upon FBPs-B(a)P0 treatment (Figure 6B, P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…Our results are consistent with the study conducted by Sun et al [41], which showed that CuO NPs induce autophagic cell death in A549 cells. Evidence of the involvement of autophagy after exposure to ZnO NPs was reported in a recent study by Liu et al, in which autophagy was identified as the main mechanism of cell death involved in response to ZnO NPs [42]. Altogether, this evidence once again confirms the less toxic potential of CuO NPs when in mixture with DEPs, and the slightly higher toxic potential of DEP + ZnO compared to ZnO NPs alone.…”
Section: Discussionsupporting
confidence: 67%
“…There was an increase in ROS levels when treated with UV-C mediated ZnONPs (2632.9 ± 234.12 relative DHR123 fluorescence units). The overgeneration of ROS by the liberation of Zn 2+ ions from ZnONPs resulted in mitochondrial dysfunction in PC 12 cells [67]. Amongst all NPs, UV-C mediated bimetallic Ag-ZnONPs (0.1/0.5) produced the highest level of intracellular ROS/RNS, showing the enhanced properties of bimetallic alloys.…”
Section: Measurement Of Intracellular Ros/rns Productionmentioning
confidence: 96%